Análisis e interpretación a los Estados Financieros del Sindicato de Choferes Profesionales de Catamayo, Provincia de Loja, periodos 2021-2022 - Pogo Nole, Orli David (2024)
The present Work of Curricular Integration called "Financial Analysis of the Professional Drivers Union of Catamayo Canton, province of Loja, Period 2021 - 2022", was developed with the purpose of fulfilling the proposed objectives of analyzing the financial-economic structure of the Union. In order to comply with the objectives, the Vertical and Horizontal analysis was applied, which will allow identifying the financial and economic structure, as well as the variations of the accounts that conform it; within the same regarding the Assets, the Union has a predominance in the Property, Plant and Equipment account, i.e. the investments made by the General Secretary, with the authorization of the General Assembly for the operation of the organization. The liabilities are $494,847.93, the item that had the highest representation is accounts and documents payable with a value of $317,839.97, this is due to the fact that the Union has contracted obligations with suppliers to acquire raw material for the works of expansion and improvement of the main road. In the application of the horizontal analysis it is evidenced that the behavior of the groups in the income statement the total income of the year 2021-2022 is determined that the Income in the year 2021 and 2022 have $5,792,159.63 and $7,097,581.37 respectively, presents a decrease of $- 1,305,421.74; it is determined that in the first year there is deficiency on the part of the partners, due to the noncompliance of the payment of monthly payments that each partner contributes. In the application of the financial indicators we found ratios that present problems and that do not reach the established standard such as: Accounts Payable Turnover in the year 2021 with 3.31 and in 2022 with 1.18, being below the standard which is 6 to 12 times, Average Payment Period with 110.12 and 310.55 for the year 2021 and 2022 the established standard is 30 to 60 days, Inventory Turnover with 80.34 and 90.72 for the years 2021 and 2022 the established standard is 6 to 10 times, Liabilities to Assets ratio of 20.79% and 31% for the years 2021 and 2022 the established standard is 40% to 60%, Short Term Leverage of 18.28% and 39.82% for the years 2021 and 2022 the established standard is 50%, this is necessary to make decisions and improvements within the Union. The preparation of the financial analysis report will allow to observe the findings obtained from the application of vertical and horizontal analysis, financial indicators, conclusions and recommendations of the financial structure and thus contribute to the decision making by its directors and contribute as financial information for its partners.